(untitled) (ESMAT Magazine, 2024)
The objective of this present work is to deal with the uses of technology in notarial and registration activities, based on the so-called “phases of automation” proposed by Manuel Castells, and the decision in the Direct Action of Unconstitutionality 2.622-DF that dealt with the mandatory transfer of the Property Registration System (SREI) for the National Operator of the Electronic Real Estate Registration System (ONR). The starting point was a bibliographical research, with a qualitative approach, using the deductive method. The work is justified by the relevance of the extrajudicial forum and the influence of new technologies on the sector. It is concluded that notary and registry activities have adapted to the demands of virtualization and even anticipated technologies and the need to improve legal and business security, even in a permanently changing environment.